Participatory methods and earthen construction in urban slums of Argentina (REVISTA NODO, 2019)
The aim of this research is the development of participative methods and alternative earth building materials and elements for housing in the poor urban contexts of Argentina. The urban poverty and the Social Technology theories were been considered to define the objectives. Fieldwork was developed with the participation of the vulnerable population in neighborhoods of Mar del Plata and Buenos Aires’s cities. The methodology is focused on the participative management methods to generate the new elements into the emergency contexts, and the appropriation by the local builders. Are introduced technical innovations based on the use of natural materials and elements with stabilized soils, and its combination with conventional industrial building materials, elements, and techniques. Are involved self builders, technicians, professionals, students, volunteers, enterprises, municipalities, and NGOs. Are built and studied different prototypes of alternative floors, walls, plasters and domiciliary stoves using earth building techniques and mixed building techniques.
Keywords: social technology; housing; earthen construction